PERLINDUNGAN HUKUM TERHADAP HASIL KARYA ARTIFICIAL INTELLIGENCE DALAM PERSPEKTIF HAK CIPTA DI INDONESIA - Cokorda Gede Yasnu Suwargita; I Nyoman Suandika; I Gusti Agung Ika Laksmi Mahadewi (Yayasan Nusantara Hasana Berdikari, 2025)
The rapid development of Artificial Intelligence (AI) presents new challenges to the Indonesian legal system, particularly in relation to copyright protection. On the one hand, AI is capable of producing creative works that resemble human creations; on the other hand, its existence raises fundamental questions regarding the legal status of such works and the applicable copyright protection. This condition demonstrates the urgency of comprehensive regulation to ensure a balance between technological innovation and legal protection. The purpose of this study is to analyze the urgency of establishing specific regulations on AI to address potential copyright infringements in Indonesia. The research employs a normative juridical method, using statutory, conceptual, and comparative approaches. Data sources are obtained through library research on national laws and regulations, international legal instruments, and relevant academic literature. The results of the study indicate that existing regulations in Indonesia, such as the Copyright Law and the Electronic Information and Transactions Law (ITE Law), still contain vague norms and have not explicitly accommodated the phenomenon of AI-based works. A comparison with regulations in the European Union through the AI Act highlights the importance of a clear legal framework concerning liability, protection of creative works, and supervisory mechanisms for the use of AI. The conclusion of this study emphasizes that specific regulation on AI in Indonesia is an urgent necessity. Such regulation must be designed to provide legal certainty regarding AI-based works while still ensuring fairness for all segments of society.